1990
DOI: 10.1159/000146859
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Fetal Mouse Palate in Suspension Organ Culture

Abstract: Explanted palates of day 12 and day 13 mouse fetuses were cultured in a chemically defined serumless medium for 48–72 h by a suspension culture technique. The palate of day 12 fetuses closed successfully within 72 h and that of day 13 fetuses within 48 h. Both macroscopically and histologically the in vitro fusion of palatal shelves simulated the palatogenetic process in vivo. This novel technique for culturing the fetal mouse palate may be of potential use for the study of palatogenesis and in developmental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 9 publications
3
69
0
Order By: Relevance
“…1A). Thus, the process of macroscopic palatal fusion in vitro basically simulated that occurring in vivo, as observed previously (Shiota et al, 1990). Grossly, palatal fusion was observed in 92% of the palates in the control group cultured for 24 hours.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…1A). Thus, the process of macroscopic palatal fusion in vitro basically simulated that occurring in vivo, as observed previously (Shiota et al, 1990). Grossly, palatal fusion was observed in 92% of the palates in the control group cultured for 24 hours.…”
Section: Resultssupporting
confidence: 74%
“…We confirmed that the suspension culture of fetal mouse palates in roller bottles (Shiota et al, 1990) was superior to static culture systems where explants were placed on Millipore filters and subjected to submerged culture. In such static cultures, nonphysiological massive cell death occurred in explants and the cultured tissues easily became necrotic (data not shown).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To understand whether the intrinsic factors are impaired in Cyp26b1À/À fetuses, we performed fetal palate culture in suspension (Shiota et al, 1990) (Fig. 5A-D).…”
Section: Cyp26b12/2 Mouse Fetuses Have Cleft Palatementioning
confidence: 99%
“…Fetal Mouse Palate in Suspension Organ Culture E13.5 palatal shelves were cultivated in suspension for 20 hr as previously described (Shiota et al, 1990). Briefly, they were placed into a sterile 15-ml glass bottle containing 1.5 ml of BGJ-b (Gibco-Life Technologies, Gaithersburg, MD), 6 mg/ml of BSA, and 150 mg/ml of ascorbic acid.…”
Section: Proliferation and Apoptosis Assaymentioning
confidence: 99%